A discrete truncated Zipf distribution. (11th October 2022) - Boamah‐Addo, Kwame; Kozubowski, Tomasz J.; Panorska, Anna K.
Abstract: We provide a comprehensive account of fundamental properties of a truncated discrete Zipf distribution, complementing the results available in the literature. In particular, we obtain results on existence and uniqueness of maximum likelihood parameter estimators and propose new testing methodology for the shape parameter. We also include data examples illustrating applicability of this stochastic model.